C1r Upregulates Production of Matrix Metalloproteinase-13 and Promotes Invasion of Cutaneous Squamous Cell Carcinoma - Viiklepp Kristina; Nissinen Liisa; Ojalill Marjaana; Riihilä Pilvi; Kallajoki Markku; Meri Seppo; Heino Jyrki; Kähäri Veli-Matti (Elsevier, 2022)
Cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer, with increasing incidence worldwide. Previous studies have shown the role of the complement system in cSCC progression. In this study, we have investigated the mechanistic role of serine proteinase C1r, a component of the classical pathway of the complement system, in cSCC. Knockout of C1r in cSCC cells using CRISPR/Cas9 resulted in a significant decrease in their proliferation, migration, and invasion through collagen type I compared with that of wild-type cSCC cells. Knockout of C1r suppressed the growth and vascularization of cSCC xenograft tumors and promoted apoptosis of tumor cells in vivo. mRNA-sequencing analysis after C1r knockdown revealed significantly regulated Gene Ontology terms cell-matrix adhesion, extracellular matrix component, basement membrane, and metalloendopeptidase activity and Kyoto Encyclopedia of Genes and Genomes pathway extracellular matrix‒receptor interaction. Among the significantly regulated genes were invasion-associated matrix metalloproteinases (MMPs) MMP1, MMP13, MMP10, and MMP12. Knockout of C1r resulted in decreased production of MMP-1, MMP-13, MMP-10, and MMP-12 by cSCC cells in culture. Knockout of C1r inhibited the expression of MMP-13 by tumor cells, suppressed invasion, and reduced the amount of degraded collagen in vivo in xenografts. These results provide evidence for the role of C1r in promoting the invasion of cSCC cells by increasing MMP production.